Impact of Oral Health Education and a Non-Surgical Periodontal Therapy on the Quality of Life of Patients with Diabetes Mellitus* - Oanta Cornelia; Pasarin Liliana; Ursarescu Irina; Martu Alexandra; Martu Silvia (Balkan Stomatological Society, 2015)
Aim: The aim of the study was to evaluate the impact of oral health education and non-surgical periodontal therapy on the quality of life for a group of patients with type I diabetes mellitus, in Iasi, Romania.